Post-Secularism as a Basis of Dialogue between Philosophy and Religion - Otto Gusti Ndegong Madung (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2021)
This article tackles the problem of religious radicalism. Religious radicalism is here interpreted as a protest against the pathology of secularism characterized by the privatization of religion. The privatization of religion is a process in which religion is regarded as an irrational and personal element, so that it cannot play a public role. In order to meet the pathology of privatization, this article offers the paradigm of post-secularism as proposed by Juergen Habermas that opens up the possibility for religion to actively participate in the public sphere. Furthermore, this writing argues that in post-secular society characterized by the public role of religion, it is essential to build a democratic and rational dialogue between religion and philosophy, faith and reason. A bridge that connects both is public reason. This article also shows that the post-secular condition opens up opportunities for theology to promote tolerance in a pluralistic society and to strengthen the public engagement of religion. This can avoid reducing religion to private piety without public responsibility while promoting the public engagement in religion in order to liberate the marginalized and oppressed.